Financial Ratios on Reducing Financial Distress Moderated by ESG Disclosure - Dina Nilam Rosalika; Nurul Fauziah; Martdian Ratna Sari (Jurnal Reksa, 2024)
This study investigates the impact of financial ratios—including leverage, liquidity, operational capacity, and operating cash flow—on financial distress while assessing the moderating influence of ESG disclosure. It focuses on 26 energy sector companies listed on the IDX from 2018 to 2022, employing a quantitative approach and purposive sampling method. Nine hypotheses were formulated and tested using multiple and moderated regression analysis. The study found that leverage has a significant negative effect on reducing financial distress. In contrast, liquidity, operating capacity, and operating cash flow ratios were found to impact reducing financial distress positively. This study also confirmed that ESG disclosure could weaken the relationship between liquidity and potential financial distress reduction. However, ESG disclosure does not mediate the relationship between leverage, operating capacity, and operating cash flow to financial distress reduction. This findings lend credence to the applicability of stakeholders theory in explaining the relationship between financial ratios, ESG disclosure and financial distress. It also provides insight for companies on how to prevent and mitigate financial distress. Companies, especially in the Energy Sector, could reduce the potential financial distress by optimizing both financial and non-financial aspects in their annual and sustainability reports.